Synergistic Anti-MRSA Activity of Cationic Nanostructured Lipid Carriers in Combination With Oxacillin for Cutaneous Application - Alalaiwe, Ahmed; Wang, Pei-Wen; Lu, Po-Liang; Chen, Ya-Ping; Fang, Jia-You; Yang, Shih-Chun (Frontiers in Microbiology, 2018)
anoparticles have become a focus of interest for their capacity as antibacterial agents. The aim of this study was to evaluate the anti-methicillin-resistant Staphylococcus aureus (MRSA) activity of cationic nanostructured lipid carriers (NLC) combined with oxacillin against ATCC 33591 and clinical isolate. The cationic resource on the NLC surface was soyaethyl morpholinium ethosulfate (SME). NLC loaded with oxacillin was produced to assess antibacterial activity and the effectiveness of topical application for treating cutaneous infection. The hydrodynamic diameter and zeta potential of oxacillin-loaded NLC were 177 nm and 19 mV, respectively. Oxacillin exhibited synergistic MRSA eradication when combined with NLC. The minimum bactericidal concentration (MBC) of oxacillin decreased from 250 to 62.5 μg/ml after NLC encapsulation. The combined NLC and oxacillin reduced the MRSA biofilm thickness from 31.2 to 13.0 μm, which was less than the effect of NLC (18.2 μm) and antibiotic (25.2 μm) alone. The oxacillin-loaded NLC showed a significant reduction in the burden of intracellular MRSA in differentiated THP-1 cells. This reduction was greater than that achieved with individual treatment. The mechanistic study demonstrated the ability of cationic NLC to disrupt the bacterial membrane, leading to protein leakage. The cell surface disintegration also increased oxacillin delivery into the cytoplasm, activating the bactericidal process. Topical NLC treatment of MRSA abscess in the skin decreased the bacterial load by log 4 and improved the skin’s architecture and barrier function. Our results demonstrated that a combination of nanocarriers and an antibiotic could synergistically inhibit MRSA growth. This could be a potential approach to resolving the risk of drug resistance.